(untitled) (World Bulletin of Social Sciences, 2023)
The article explores one of the important areas of modern ethics, bioethics, and the area of its research. The article focuses on the practical uniqueness of the Universal Declaration on Bioethics and Human Rights, which governs all aspects relating to man. Some sources related to bioethical problems are considered and how bioethics relates to the block of general theoretical philosophical sciences. The main concepts, rules and principles and problems of global ethics and bioethics are highlighted.